2022
DOI: 10.21608/asnj.2022.117326.1306
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Reported Practices for Mothers of Phenylketonuria Children at Hereditary Guideline Center in Assiut Governorate

Abstract: Background: Phenylketonuria is an inherited autosomal recessive metabolic disorder that causes elevated blood phenylalanine concentrations. Aim of the study: To assess knowledge, attitude and reported practices of mother with phenylketonuria children at Hereditary Guideline Center in Assiut Governorate. Methods: Descriptive research design was used in this study. The total sample number of the studied sample was 360 mothers. Convenience sample was used Tools of the study: personal interview questionnaire which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…In a similar study conducted in UAE, the researchers have found that 74.0% of the participants had good knowledge of DS and 67.2% of them had positive attitude towards the patients suffering from DS. Unlike the present study 85% of the participants were aware of the fact that DS is the most common cause of intellectual disability globally [9]. Comparatively, good knowledge (70.0%) and favorable attitude (78.0%) towards DS was also found in one Indian study where only 30% of the participants were having poor knowledge and 22% had unfavorable attitude [10].…”
Section: Discussioncontrasting
confidence: 67%
“…In a similar study conducted in UAE, the researchers have found that 74.0% of the participants had good knowledge of DS and 67.2% of them had positive attitude towards the patients suffering from DS. Unlike the present study 85% of the participants were aware of the fact that DS is the most common cause of intellectual disability globally [9]. Comparatively, good knowledge (70.0%) and favorable attitude (78.0%) towards DS was also found in one Indian study where only 30% of the participants were having poor knowledge and 22% had unfavorable attitude [10].…”
Section: Discussioncontrasting
confidence: 67%